KETANGGUHAN WILAYAH PESISIR SELATAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA TERHADAP BAHAYA BENCANA TSUNAMI - Mega Kusuma Dewi; Doddy Aditya Iskandar (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
The southern coastal region of the Special Region of Yogyakarta (DIY) has a high vulnerability to the risk of tsunami. This disaster risk is certainly endangering the people who live in this area. In addition, this risk can also be a factor that hinders development in the DIY’s coastal area. Therefore, in order to reduce the negative impacts, this area must be resilient to a tsunami disaster. This study is an effort to measure the regional resilience against the tsunami risk in 13 sub-districts on the south coast of DIY. The measurement uses a calculation method adapted from the theory of spring elasticity. The finding demonstrates subdistricts in the SRY have low to moderate level of resilience to tsunami disaster.